1981
DOI: 10.1177/002234338101800301
|View full text |Cite
|
Sign up to set email alerts
|

Capitalism and Armaments: Business Cycles and Defense Spending in the United States 1945—1979

Abstract: Three possible economic explanations of U.S. military spending are examined: 1) the MIC explanation, 2) the economic stabilization and electoral defense cycle explanation, 3) the capitalist growth imperative explanation. Conditions for these explanations to be valid are formulated and tested with data about the development of defense spending, the U.S. economy, the business cycle, and fiscal policy, as well as an analysis of the Economic Reports and of secondary sources about U.S. defense and economic policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Thus, from a Keynesian perspective, since greater military outlay is not offset by the contraction induced by higher taxes, wars typically cause a short-term economic boom boosting aggregate demand and consumption. As argued by Nincic & Cusack (1979) and Krell (1981), this is one of the main economic explanations of increases in military spending. However, Barker, Dunne & Smith (1991) have shown that such increases have contractionary effects on the UK economy.…”
Section: Private Consumption and The Financing Mechanism Of Military mentioning
confidence: 91%
“…Thus, from a Keynesian perspective, since greater military outlay is not offset by the contraction induced by higher taxes, wars typically cause a short-term economic boom boosting aggregate demand and consumption. As argued by Nincic & Cusack (1979) and Krell (1981), this is one of the main economic explanations of increases in military spending. However, Barker, Dunne & Smith (1991) have shown that such increases have contractionary effects on the UK economy.…”
Section: Private Consumption and The Financing Mechanism Of Military mentioning
confidence: 91%
“…The factors accounting for this variation can be subdivided into external or international variables and domestic variables. External variables that have been correlated with a state's military spending include the state's overall strategic environment (Krell, 1981;Lebovic & Ishaq, 1997), the relative spending of its rivals (Hartley & Russett, 1992;Hewitt, 1992;Mintz & Ward, 1989;Nordhaus et al, 2012) and strategic rivals (Dunne & Perlo-Freeman, 2003;Fordham & Walker, 2005;Rosh, 1988), arms races Ostrom & Marra, 1986;Richardson, 1960), alliances (Olson & Zeckhauser, 1966;Murdoch & Sandler, 1984), and geography (Hewitt, 1992). International economic conditions such as development aid (Collier & Hoeffler, 2007) and sanctions and embargoes have also been found to impact spending (Batchelor et al, 2002).…”
Section: Existing Literature On Military Spendingmentioning
confidence: 99%
“…His analysis focuses on revenues and competing expenditure items and seeks to show that defense is (a) weak contender in the competition for scarce federal resources and (b) one that can acquire, for a limited period, greater resources when international events appear (in the public imagination) to threaten the security of the United States. 17 Gert Krell (1981), in a long and detailed recounting of post-World War II economic tendencies within the U.S. has attempted to evaluate the plausibility of what he describes as three "economistic" models of American military spending. These included (1) the military industrial complex notion, (2) the capitalist growth imperative idea, and (3) our argument with respect to the impact of economic stabilization and the electoral cycle.…”
Section: Proportion Expressing Concern With the Economymentioning
confidence: 99%